Metallurgical properties and biomimetic HA deposition performance of Ti-Nb PIM alloys - (:unkn) unknown (ELSEVIER SCIENCE SA, 2018)
Ti-Nb alloys are potential candidates owing to their excellent mechanical properties and high corrosion resistance for bioactive implant applications compared to other metallic materials. The purpose of this work is to investigate the effect of the Nb amount on the microstructure, mechanical properties, corrosion behavior and hydroxyapatite (HA) formation ability of Ti-Nb alloys produced via powder injection molding. According to the phase/microstructure studies, including XRD analyses, optical microscope, and SEM imaging, all of the alloys are composed of alpha+beta phases, and with the increment of Nb content, beta phase stability increases. Also, it is observed that Nb content has significant effects on the mechanical properties of the considered alloys. While the hardness/Transverse rupture strength values of Ti-Nb alloys (303-340HV, 992-440 MPa) are higher than that of the titanium (269HV, 300 MPa), the elastic modulus is measured as lower than (100-115 GPa) that of the titanium (132-140 GPa). The increment of Nb content causes to decrease of the hardness, bending strength and elastic modulus of Ti-Nb alloys. Also, the addition of Nb contributed to the improvement of corrosion resistance and induced to increase of hydroxyapatite formation ability. (c) 2018 Elsevier B.V. All rights reserved.
Keywords: Metallurgical characterization; Titanium alloys; Powder methods; Biomaterials; MECHANICAL-PROPERTIES; CORROSION BEHAVIOR; MICROSTRUCTURAL EVOLUTION; TITANIUM IMPLANTS; BIOCOMPATIBILITY; BETA; PARAMETERS; COATINGS; FILM